Recovering Christian Realism Just War Theory as a Political Ethic - Baer, H. David (Helmut David), 1968- (Lanham : Lexington Books, 2014)
Recovering Christian Realism develops an account of just war theory as a political ethic grounded explicitly in a Christian theory of political authority. It advances a defense of Christian realism, explains the role played by power in peacemaking, and suggests the outlines for a Christian theory of international relations.
Power, peace, and the just war ethic -- The criterion of legitimate authority : describing the political act -- The criterion of just cause : the limits on government's international jurisdiction -- The criterion of just intention : the pursuit of peace and international order -- Justice in bello : applying the principle of discrimination -- The just war ethic and the nature of Christian realism.
Description based upon print version of record.
Keywords: War -- Moral and ethical aspects; War -- Religious aspects -- Christianity; Just war doctrine; Just war doctrine; War -- Moral and ethical aspects; War -- Religious aspects -- Christianity; RELIGION / Christian Theology / Ethics; Electronic books